• Matéria: Matemática
  • Autor: rayssa19052002
  • Perguntado 5 anos atrás

me ajudem por favor​

Anexos:

Respostas

respondido por: fairchildclary
0

a)

( { \frac{1}{8} })^{ - 2}  =  {8}^{2}  = 64 \\  \\(  { \frac{1}{2} })^{4}  =  \frac{ {1}^{4} }{ {2}^{4} }  =  \frac{1}{16}  \\  \\ 64 \times  \frac{1}{16}  =  \frac{64}{16}  = 4

b)

 ({ \frac{1}{4} })^{0}  = 1 \\  \\ ( { \frac{1}{2} })^{3}  =  \frac{ {1}^{3} }{ {2}^{3} }  =  \frac{1}{8}  \\  \\ \frac{1}{3}  \times  \frac{1}{8}  =  \frac{1}{24}  \\  \\ 1 -  \frac{1}{24}  =  \frac{23}{24}

Perguntas similares